Oral administration of Huanglian-Houpo herbal nanoemulsion loading multiple phytochemicals for ulcerative colitis therapy in mice - Xiao Wang; Li Fu; Weijian Cheng; Jiamei Chen; Huan Zhang; Huanjun Zhu; Chen Zhang; Chaomei Fu; Yichen Hu; Jinming Zhang (Taylor & Francis Group, 2023)
AbstractHow to achieve stable co-delivery of multiple phytochemicals is a common problem. This study focuses on the development, optimization and characterization of Huanglian-HouPo extract nanoemulsion (HLHPEN), with multiple components co-delivery, to enhance the anti-ulcerative colitis (UC) effects. The formulation of HLHPEN was optimized by pseudo-ternary phase diagram combined with Box-Behnken design. The physicochemical properties of HLHPEN were characterized, and its anti-UC activity was evaluated in DSS-induced UC mice model. Based on preparation process optimization, the herbal nanoemulsion HLHPEN was obtained, with the droplet size, PDI value, encapsulation efficiency (EE) for 6 phytochemicals (berberine, epiberberine, coptisine, bamatine, magnolol and honokiol) of 65.21 ± 0.82 nm, 0.182 ± 0.016, and 90.71 ± 0.21%, respectively. The TEM morphology of HLHPEN shows the nearly spheroidal shape of particles. The optimized HLHPEN showed a brownish yellow milky single-phase and optimal physical stability at 25 °C for 90 days. HLHPEN exhibited the good particle stability and gradual release of phytochemicals in SGF and SIF, to resist the destruction of simulated stomach and small intestine environment. Importantly, the oral administration of HLHPEN significantly restored the shrunk colon tissue length and reduced body weight, ameliorated DAI value and colon histological pathology, decreased the levels of inflammatory factors in DSS-induced UC mice model. These results demonstrated that HLHPEN had a significant therapeutic effect on DSS-induced UC mice, as a potential alternative UC therapeutic agent.